2012
DOI: 10.1016/j.cej.2012.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Impact of NOM character on copper adsorption by trace ferric hydroxide from iron corrosion in water supply system

Abstract: The fate of trace concentrations of cupric sulphate (< 0.4 mg/L) dosed into chloraminated distribution systems to inhibit nitrification has been shown in this study to be controlled by at least two crucial factors: the character of natural organic matter (NOM) and iron hydroxide corrosion products present at low concentrations (< 2 mg/L). This research quantified the removal of Cu(II) ions added into waters containing trace Fe(OH) 3 flocs and the effect of NOM of different character on this removal. The domina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
0
6
0
Order By: Relevance
“…In chloraminated systems, Cu speciation will be controlled by various factors, including pH, NOM concentration and its complexing ability, and free ammonia. For example, in the case of Mundaring water used for this study, Cu-NOM complexes were the major species present (Zhan et al, 2012). Therefore, future studies should concentrate on understanding Cu speciation and its impact on nitrifiers in the chloraminated environment.…”
Section: Implications Of the Results For Full Scale Systemmentioning
confidence: 96%
See 3 more Smart Citations
“…In chloraminated systems, Cu speciation will be controlled by various factors, including pH, NOM concentration and its complexing ability, and free ammonia. For example, in the case of Mundaring water used for this study, Cu-NOM complexes were the major species present (Zhan et al, 2012). Therefore, future studies should concentrate on understanding Cu speciation and its impact on nitrifiers in the chloraminated environment.…”
Section: Implications Of the Results For Full Scale Systemmentioning
confidence: 96%
“…Following the Australian Drinking Water Quality Guidelines (ADWG, 2004) and authorized by the Department of Public Health, Western Australia, copper doses of 0.25e0.40 mg-Cu L À1 were applied in a part of the distribution system. The results showed that nitrification could be controlled by dosing copper into service reservoirs and pipelines, although an impediment was the significant loss of copper during transport through the corroded iron pipeline (Zhan et al, 2012). Several processes can significantly affect the copper concentration in the pipelines compared to the reservoir.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…While pH plays an important role in the speciation of copper (i.e., copper ion levels decrease significantly under alkaline pH), silver ions are relatively stable in the pH range of 6-9. Some chemical parameters (e.g., chloride and phosphates added for chlorination and corrosion control, respectively) react with copper and silver ions, and consequently these metal complexes diminish their microbiocidal power [111][112][113]. Moreover, the latter metal complex chlorargyrite (AgCl (s) ) contributes to the purple/grey stains in bathroom porcelain [114].…”
Section: Copper-silver Ionization (Csi)mentioning
confidence: 99%